2020
DOI: 10.1093/mnras/staa1999
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the Milky Way’s Central Molecular Zone – II. Star formation

Abstract: Abstract The Milky Way’s central molecular zone (CMZ) has emerged in recent years as a unique laboratory for the study of star formation. Here we use the simulations presented in Tress et al. 2020 to investigate star formation in the CMZ. These simulations resolve the structure of the interstellar medium at sub-parsec resolution while also including the large-scale flow in which the CMZ is embedded. Our main findings are as follows. (1) While most of the star for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 101 publications
2
49
0
Order By: Relevance
“…Comparison to Other Simulations -In our models the SN feedback alone induces a factor of ∼ 2 fluctuations of the SFR with timescale 40 Myr (see also Paper I). This appears consistent with the results of the global simulations of Sormani et al (2020) who found that the 4 Although the two spiral arm model seems to place the Sgr B2 complex and brick at the far side, the absorption and proper motion data strongly suggest that they are at the near side. Ridley et al (2017) reconciled this inconsistency by suggesting that those clouds are kinematically detached, jutting out of the nearside arm.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Comparison to Other Simulations -In our models the SN feedback alone induces a factor of ∼ 2 fluctuations of the SFR with timescale 40 Myr (see also Paper I). This appears consistent with the results of the global simulations of Sormani et al (2020) who found that the 4 Although the two spiral arm model seems to place the Sgr B2 complex and brick at the far side, the absorption and proper motion data strongly suggest that they are at the near side. Ridley et al (2017) reconciled this inconsistency by suggesting that those clouds are kinematically detached, jutting out of the nearside arm.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…In global simulations of nuclear rings (e.g., Seo et al 2019;Armillotta et al 2019;Sormani et al 2020;Tress et al 2020), the inflow rate is naturally time variable and feedback is always active following star formation, so that it is difficult to discern what dominates in shaping the star formation history of nuclear rings. To separate the effects of feedback from those of the mass inflow, Moon et al (2021, hereafter Paper I) designed semiglobal models that focus on nuclear rings and nearby regions, handling the bar-driven mass inflows along dust lanes by gas streams through two nozzles located at the domain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…This dust-ridge is thought to be connected to the ionised ridge via a ring of material surrounding the Galactic Centre found in simulations (e.g. Sormani et al 2018;Dale et al 2019a;Kruijssen et al 2019a;Sormani et al 2020;Tress et al 2020) and extragalactic systems (e.g. Comerón et al 2010;Krieger et al 2020), which is maintained by the inflow of material from the bar (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…The emerging picture is therefore the following: most of the mass of the NSD formed shortly after the formation of the bar > 8 Gyr ago. Then, from 8 Gyr ago to the present day, the NSD has grown further at variable rates depending on the rate of SFR in the CMZ, which is regulated by the amount of fresh gas available through the bar-driven inflow and possibly by internal feedback cycles (for discussions on what controls the star formation rate in the CMZ see for example Kruijssen et al 2014;Krumholz et al 2017;Armillotta et al 2019;Sormani et al 2020a;Moon et al 2021b,a).…”
Section: Formation and Evolution Of The Nsdmentioning
confidence: 99%